Diagnostic Accuracy of Cognitive Screening Instruments in Heart Failure: A Systematic Review. Issue 5 (September 2016) - Cameron, Jan; Kure, Christina E.; Pressler, Susan J.; Ski, Chantal F.; Clark, Alexander M.; Thompson, David R.
Abstract : Background: Cognitive impairment is prevalent in heart failure (HF) with severe consequences, including increased risk of mortality and reduced ability to self-manage HF symptoms. Identifying cognitive impairment through screening would assist clinicians in managing HF and comorbid cognitive impairment. However, the accuracy of cognitive screening instruments for HF has not been adequately determined. Objective: The aim of this study was to determine the diagnostic accuracy of cognitive screening instruments in screening for mild cognitive impairment (MCI) in HF patients. Methods: A systematic review of major electronic bibliographic databases was searched from January 1999 to June 2013. Inclusion criteria were as follows: primary studies examining cognitive impairment in HF, administration of a cognitive screening instrument and neuropsychological test battery, and cognitive impairment indicated by performance on neuropsychological tests 1.5 SDs less than that of normative data. Methodological rigor of included publications was evaluated using2 bias risk instruments: QUality Assessment of Diagnostic Accuracy Studies and STAndards for the Reporting of Diagnostic accuracy studies. The precision, accuracy, and receiver operating characteristic curves of the Mini Mental State Examination were computed. Results: From 593 citations identified, 8 publications met inclusion criteria. Risk of bias included selective HF patient samples, and no study examined the diagnostic test accuracy of the cognitive screening instruments. The Mini Mental State Examination had low sensitivity (26%) and high specificity (95%) with a score of 28 or less as the optimal threshold for MCI screening. Conclusions: Screening for cognitive impairment in HF is recommended; however, future studies need to establish the diagnostic accuracy of screening instruments of MCI in this population.